Factores internos y externos en la categorización fonológica de pistas acústicas - Vida-Castro, Matilde Ángeles (My University, 2018)
The aim of this paper is to show and discuss the results obtained in a perceptual experiment carried out in the frame of the study of syllable-final /-s/ variation in Malaga. In this particular variety, when syllable-final /-s/ is followed by the voiceless dental plosive phoneme /t/, it is frequently realized (pronounced?) as an alveolar affricate sound [ts] which can also be an allophone of the palatal affricate Spanish phoneme /ʧ/. The use of this variant makes it difficult to distinguish minimal pairs such as mosto ‘grape juice’ and mocho ‘mop’, realized respectively as [mótso] and [móʧo]. The results of the experiment suggest that, although there are consistent acoustic cues listeners connect to either /s/ or /ʧ/ and the effect of external factors show a relationship between production and perception, lexical discrimination can decisively influence phoneme categorization.
Keywords: Fonética acústica; Percepción; Español meridional; Cambio lingüístico